From minding the gap to widening the gap: Paralympic athletes' experiences of wellbeing during the postponement of the Tokyo 2020 games - Budon, A.; Trainor,L. R.; Bennett, E. V.; Tremblay, M. I.; Mannella, S.; Crocker, P. R. E. (Frontiers in Sports and Active Living, 2022)
In March 2020, it was announced that the Tokyo Games would be postponed for one year due to the COVID-19 pandemic. While athletes commonly face challenges in sport such as injuries, the pandemic and rescheduling of the Games was an unexpected event that had serious potential to challenge the psychological wellbeing of athletes. Furthermore, it was an event that was simultaneously experienced by all athletes preparing for the Games. It provided a novel opportunity to explore how athletes navigated this challenging environment and the subsequent potential impact on their psychological wellbeing. It also provided a unique opportunity to engage para-athletes and explore how they experienced the pandemic and postponement. This manuscript draws on a larger qualitative study of 21 Canadian athletes (14 Olympic and seven Paralympic) who were on target to compete at the 2020 Games when the postponement was announced. For this manuscript, we focus on the accounts of seven Paralympic hopefuls and their experiences of adjusting to the postponement, while attending to the unique social identities of athletes with disabilities. Adopting a constructionist lens, semi-structured interviews were conducted at two time points. Through reflexive thematic analysis, we developed three themes. "We are all in the same boat. . . or are we?" describes the Paralympic hopefuls experiences early in the pandemic and how they felt united by the Canadian response to withdraw from the Games. It then discusses how, over time, they started to understand athletes with disabilities were being inequitably impacted by the pandemic and related public health measures. "Maybe it means more to them than us" examines how their perceptions changed as they acknowledged that although all athletes were facing a disruption to their sport careers, the implications were not the same for all. "Vulnerability and the Paralympic athlete" addresses how Paralympic athletes engaged with societal narratives about risk, vulnerability and disability and what this meant for the Paralympic Movement's response to the pandemic. "Honestly, I've experienced it before" examines how the Paralympic hopefuls drew on past experiences of injury to navigate the pandemic and the protective impact on their psychological wellbeing. Findings shed light on how systemic ableism interacted with the pandemic to magnify feelings of inferiority and further marginalization but also how para-athletes drew on past experiences to navigate challenges to their psychological wellbeing.